The structure and genesis of non-psychotic psychopathology in persons who undergo opioid substitution maintenance therapy - Gorodokin, A.; Городокін, Антон Дмитрович (My University, 2019)
Introduction. Substitution Maintenance Therapy (SMT) has now received the status of a conventional treatment for opioid dependence in Ukraine. It has been introduced since 2005, and by 2018 more than 9.000 patients are systematically receiving SMT. The data obtained in previous part of this study by applying the diagnostic tools for neurotic symptoms on the contingent of 100 SMT patients had shown that near 95% contingent are suffering from non-psychotic anxiety, depression, asthenia, conversion, obsessive and phobic symptoms of mixed origin. Objective. To characterize the manifestations, establish the intensity and describe the predictors of non-psychotic psychopathology symptoms in SMT patients. Materials and methods. The study was conducted in a prospective design in the period 09.2016-03.2019 on the basis of “Regional Clinical Narcological Dispensary” Zaporizhzhya, Ukraine. The contingent of 100 patients (20 women and 80 men) diagnosed with ICD-10: F11.22 with mean age was 41,2 ± 5,6 years and the mean period of systematic use of 16,1 ± 7,4 years. Study was based on clinical assessment with “Symptom Checklist-90-Revised” and statistical methods. Results. 5 separate groups of psychopathology predictors were systemized. Role and influence on non-psychotic psychopathology was analyzed for each group of predictors. Clinical assessment with “Symptom Checklist-90-Revised” shown that in the contingent of the study are presented all groups of psychopathological symptoms, but its intensity is generally moderate (12 patients with GSI ≤0,50; 52 patients with GSI=0,51-1,50; 36 with GSI≥1,51). The analysis of correlations between psychopathological symptoms allowed revealing 6 symptom non-psychotic syndromes: anxious-obsessive (r=0,78; p≤0,05), obsessively-sensitive (r = 0,64; p≤0,05), depressively-sensitive (r=0,81, p≤0,05), depressive-dysphoric (r=0,66; p≤0,05), paranoicaly-dysphoric (r=0,75; p≤0,05), anxious-paranoic (r=0,76; p≤0,05). Conclusions. Non-psychotic psychopathological violations in persons undergoing SMT program have a complex multifactorial genesis, which leads to a distortion of their clinical manifestations which become specific; predictors of non-psychotic psychopathology in persons undergoing SMT program could be systematized into 5 groups (exogenous, organic, somatogenous, psychogenous, personologic) that makes multidirectional effect on clinical characteristics and intensity of psychopathological symptoms. Non-psychotic psychopathology in persons undergoing SMT program have a specific clinical profile − in the contingent of the study are presented all groups of psychopathological symptoms with moderate intensity. There are 6 non-psychotic syndromes, presented in SMT patients.
Keywords: Substitution Maintenance Therapy; opioid dependence; non-psychotic psychopathology